The lady and the highwayman [large type] - Eden, Sarah M. (Proper romance, 2019)
"Elizabeth Black is the headmistress of a girls' school and a well-respected author of "silver-fork" novels, stories written both for and about the upper-class ladies of Victorian society. But by night, she writes very different kinds of stories--the Penny Dreadfuls that are all the rage among the working-class men. Under the pseudonym Mr. King, Elizabeth has written about dashing heroes fighting supernatural threats and dangerous outlaws romancing helpless women. They contain all the adventure and mystery that her real life lacks. Fletcher Walker began life as a street urchin, but is now the most successful author in the Penny Dreadful market, that is until Mr. King started taking all of his readers--and his profits. No one knows who King is, including Fletcher's fellow members of the Dread Penny Society, a fraternity of authors dedicated to secretly fighting for the rights of the less-fortunate. Determined to find the elusive Mr. King, Fletcher approaches Miss Black. As a fellow-author, she is well-known among the high-class writers; perhaps she could be persuaded to make some inquiries as to Mr. King's whereabouts? Elizabeth agrees to help Fletcher, if only to insure her secret identity is never discovered. For the first time, Elizabeth experiences the thrill of a cat-and-mouse adventure reminiscent of one of her own novels as she tries to throw Fletcher off her scent. But the more time they spend together, the more she loses her heart. Its upper-class against working-class, author against author where readers, reputations, and romance are all on the line"--